1985
DOI: 10.1148/radiology.155.1.3975424
|View full text |Cite
|
Sign up to set email alerts
|

Colon perforation following percutaneous nephrostomy and renal calculus removal.

Abstract: Two patients had colonic perforation as a result of percutaneous nephrostomy placement followed by track dilatation and renal calculus removal. We present the technical aspects of nephrostomy placement and stone removal, as well as the clinical diagnosis and management of these cases. Both patients recovered well with conservative therapy and required no surgical intervention. This report reviews the anatomic considerations for percutaneous nephrostomy in patients undergoing renal stone removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(30 citation statements)
references
References 0 publications
0
28
0
2
Order By: Relevance
“…A retrorenal colon is more frequently found on the left side and is most likely to be situated near the inferior kidney pole. (11) Retrorenal colon is found in approximatively 0.6% of the general population according to the Hadar-Gadot and Sherman et al study. (12,13) In another study with 333 participants, CT images showed that the left colon was posterior in 16.1% of cases, and the right colon was posterior in 9% of cases at the level of the lower pole.…”
Section: Resultsmentioning
confidence: 94%
“…A retrorenal colon is more frequently found on the left side and is most likely to be situated near the inferior kidney pole. (11) Retrorenal colon is found in approximatively 0.6% of the general population according to the Hadar-Gadot and Sherman et al study. (12,13) In another study with 333 participants, CT images showed that the left colon was posterior in 16.1% of cases, and the right colon was posterior in 9% of cases at the level of the lower pole.…”
Section: Resultsmentioning
confidence: 94%
“…We suggested that the use of preoperative computed tomography and the more posterior site of skin puncture (at the posterior axillary line) decrease the incidence of colonic injury. Both LeRoy et al (17) and Hopper et al (18) found that only 2% of their patients had retro renal colon when supine which subsequently increased to 10% when prone. Valdivia et al (5) reported that the colon was more distant from the kidney in the supine position in comparison to the prone position after performing renal puncture in the supine position in human corpses.…”
Section: Discussionmentioning
confidence: 94%
“…T h e rarity of this anatomical arrangement is confirmed by the infrequency with which the bowel is punctured during posterior percutaneous procedures (Bonaldi et al, 1991;LeRoy et al, 1985) and by the work of Helms et a]. (1989), who reviewed prone CT studies in 346 patients before percutaneous diskectomy.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years this variation has attracted attention because of increasing interest in percutaneous renal (Reznek and Talner, 1984) and vertebral (Bonaldi et al, 1991) procedures. A posteriorly situated colon may be damaged if too posterolateral an approach is used (LeRoy et al, 1985). Hence there have been numerous articles detailing the position of the colon, as shown by CT; these have particularly considered the position in relation to the kidneys (Hadar and Gadoth, 1984;Sherman et al, 1985;Hopper et al, 1987;Helms et al, 1989;Prassopoulos et al, 1990).…”
Section: Introductionmentioning
confidence: 99%